KAJJAN PEMANENAN TERHADAP KERAPATAN TEGAKAN DI BAGIAN HUTAN ALAM TROPIS PROPINSI LAMPUNG - Wesman Endom; Ishak Sumantri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
This paper studied the logging impact on forest density in a forest concession in Province of Lampung, 38 sample plots were taken consisting of 22 plots located in virgin/not yet logged and 16 located in logged over area. The result show that :1.The initial potential of forest area can be classified as moderate, with composition of commercial wood of Dipterocarpaceae 43.9%, 14.4% Non Dipterocarpaceae and the rest 41.3% of non commercial species. The average volume of commercial wood per hectare of diameter class 50 cm and up ranged from 6 - 42 m3, and for diameter class 20 - 50 cm ranged from 7 - 48 m3 per hektar. The forest density of those two diameter classes varied from 4 - 16 trees and 16 - 64 trees per hektar, respectively.2.Forest logging operation has reduced the volume and number of commercial trees per hectare (Dipterocarpaceae and Non Dipterocarpaceae) at about 50% and 38% respectively.Compared to TPTI (Indonesian Selective Cutting System) it was found that this condition can not meet the TPTI requirements for nucleus trees for the next cutting cycle.3.The logging operation has caused the openings of land cover at about 30.54% per ha or similar to an area 3054 m2 per ha